On catatonia again... - literature review - Rudzinski, Gracjan; Brzuszkiewicz, Kinga; Pożarowska, Kinga; Kusak, Natalia; Łozowski, Borys; Szczepaniak-Wójtowicz, Elżbieta; Soroka, Ewelina (Journal of Education, Health and Sport, 2023)
Introduction: In addition to the symptoms, the symptoms of catatonia have been classified as a subtype of schizophrenia (catatonic schizophrenia). Currently, however, catatonia is treated as a single psychopathological syndrome that can occur in the course of various disorders. Catatonia has been the subject of many disputes in the scientific community over the years, and many of its elements remain unexplored. Material and method: The aim of the study is to review current research on catatonia in the field of: main, leading to catatonia, neuroimaging, immunology, methods of treatment and psychoactive compounds, COVID-19, therapy of pediatric and geriatric patients. The article reviews research and scientific papers from 2014-2022 on catatonia, interest in the PubMed and Google Scholar databases. Results: Studies showing a prevalence of catatonia of approximately 10.6 cases per 100,000 tax recipients. The assessment of the prevalence of individual catatonias varies depending on the criteria. Deep vein embolism has been confirmed in approximately 25.3% of patients with cardiac catatonia. Conclusions: Catatonia is a common neuropsychiatric syndrome that significantly prolongs hospitalization time. Additional studies using the technique of functional neuroimaging of the brain are needed. Effects of treatment with the effect of: zolpidem, memantine, amantadine and augmentation with amisulpiride.